A pilot study comparing The Borg CR Scale® (centiMax®) and the Beck Depression Inventory for scaling depressive symptoms. Issue 3 (3rd July 2019) - Borg, Elisabet; MagalhÃes, Adsson; Costa, Marcelo Fernandes; MÖrtberg, Ewa
Abstract: The Borg centiMax scale is a psychophysically constructed general intensity scale with verbal anchors placed in congruence with the numerical scale (0–100); thus, ratio data are obtained. With ratio data, quantitative relationships among perceptions and feelings can be determined in a statistically more solid way. The purpose of this pilot study was to explore the utility of using the Borg CR Scale® (centiMax ®, CR100) for measuring depressive symptoms in a pilot study of 50 students, who completed the centiMax along with the Beck Depression Inventory (BDI). Convergent validity and reliability were examined by correlation analyses (Pearson, Spearman, and Split-half with Spearman–Brown correction), and group and individual symptom profiles were constructed to illustrate the possible advantage of level anchored ratio data. The strong correlation 0.75 ( p < .001) between the instruments supports an acceptable convergent validity of the centiMax and indicates a common underlying construct. Additionally, the reliability was high (cM = 0.96; BDI = 0.90). With symptom profiles, it was demonstrated that level anchored ratio data can show both how intense (level) and how many times more intense (relation) the feelings of separate symptoms are. In conclusion, the centiMax appears to be a valid and reliable instrument; however, further studies in larger samples including clinically depressed participants are needed for evaluating its diagnostic importance.